The symbolic and the look in Eraserhead, by David Lynch - Vieira , Roberta; Nunes , Alexandre Silva (Seven Editora, 2023)
This article presents an analysis of the correlation between the dramaturgic content and the visual content of the feature film Eraserhead, by David Lynch, based on the theories of the imaginary, establishing identification and study of the symbolic material contained in the film's plot, reflecting on the relationship of this material with the choice s made by the art direction team of the work. DOI:https://doi.org/10.56238/devopinterscie-121